Assessment of osteoarthritis functional outcomes and intra‐articular injection volume in the rat anterior cruciate ligament transection model. Issue 9 (7th January 2022) - Wang, Yuyan; Wagner, Emma S.; Yu, Danqiao; Chen, Kevin J.; Keel, Taidhgin J.; Pownder, Sarah L.; Koff, Matthew F.; Cheetham, Jonathan; Samaroo, Kirk J.; Reesink, Heidi L.
Abstract: The rat surgical anterior cruciate ligament transection (ACLT) model is commonly used to investigate intra‐articular osteoarthritis (OA) therapies, and histological assessment is often the primary outcome measure. However, histological changes do not always correlate well with clinical outcomes. Therefore, this study evaluated functional outcomes in the rat surgical ACLT model and compared intra‐articular injection volumes ranging from 20 to 50 μl. Unilateral ACLT was surgically induced and static weight‐bearing, mechanical allodynia, motor function, and gait were assessed in four groups of male, Sprague‐Dawley rats ( n = 6 per group). Intra‐articular injections of 20 µl Dulbecco's phosphate‐buffered saline (DPBS), 50 µl DPBS, or 50 µl of synthetic biomimetic boundary lubricant were administered once weekly for 3 weeks postoperatively. Structural changes were evaluated histologically at 20 weeks. Rat cadaver knees were injected with 20, 30, 40, or 50 µl of gadolinium solutions and were imaged using magnetic resonance imaging (MRI). Static weight‐bearing, mechanical allodynia, and gait parameters in ACLT groups revealed differences from baseline and naïve controls for 4 weeks post‐ACLT; however, these differences did not persist beyond 6 weeks. Different intra‐articular DPBS injection volumes did not result in functional or histological changes; however, peri‐articular leakage was documented via MRI following 50, 40, and 30 µl but not 20 µl gadolinium injections. Statement of clinical significance: Differences in functional parameters were predominantly restricted to early, postoperative changes in the rat surgical ACLT model despite evidence of moderate histologic OA at 20 weeks. Injection volumes of 20–30 µl are more appropriate for investigating intra‐articular therapies in the rat knee.